Optimizing Internship Registration Process Using a Business Process Reengineering Approach - Muhammad Syifa Mubarok; Ilyas Nuryasin (bit-Tech, 2025)
The internship registration process at the Malang City Religious Court is still conducted manually, resulting in various administrative problems such as long processing times, risk of data input errors, and inefficient communication flows. These issues conflict with the principles of modern public service, which emphasize efficiency, transparency, and technology-based accessibility. This study aims to optimize the internship registration process by applying the Business Process Reengineering (BPR) approach, which involves fundamentally redesigning business processes to achieve significant improvements in performance. The approach is supported by ESIA (Eliminate, Simplify, Integrate, Automate), a technique focused on eliminating non-value-added activities, simplifying procedures, integrating fragmented processes, and implementing digital automation. This research employs a qualitative case study method involving field observations and in-depth interviews with administrative staff. The current workflow is modeled using Business Process Model and Notation (BPMN), and process performance is measured using throughput efficiency the ratio of value-added activity time to total process duration. The results reveal that the initial manual process, consisting of 38 activities with a total time of 209 minutes, was successfully transformed into a streamlined digital process with only 12 steps and a total duration of 168 seconds. Throughput efficiency increased significantly from 52.15% to 100%. In conclusion, the digitization of the internship registration process using BPR and ESIA has significantly enhanced administrative efficiency. This study contributes a replicable digital system model suitable for non-litigation public services in religious courts and enriches the BPR literature by introducing its application in public sector services rooted in religious legal institutions.